2007
DOI: 10.1116/1.2803717
|View full text |Cite
|
Sign up to set email alerts
|

Thermotunnel refrigerator with vacuum/insulator tunnel barrier: A theoretical analysis

Abstract: Thermosize effects and thermodynamic analysis of a macro/nano scaled refrigerator cycle

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 4 publications
0
18
0
Order By: Relevance
“…However, the cooling coefficient of such junctions does not exceed 10%. Further, a metal-vacuum-insulatormetal (MVIM) tunnel junction with an additional thin insulator coating layer has been studied [6]. It was found that the cooling coefficient of MVIM junction is of the order of 40-50% and, in addition, the insulating layer protects the electrodes against the short circuit and simplifies design.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the cooling coefficient of such junctions does not exceed 10%. Further, a metal-vacuum-insulatormetal (MVIM) tunnel junction with an additional thin insulator coating layer has been studied [6]. It was found that the cooling coefficient of MVIM junction is of the order of 40-50% and, in addition, the insulating layer protects the electrodes against the short circuit and simplifies design.…”
Section: Introductionmentioning
confidence: 99%
“…However, a conformal electrode method based on the electrochemical growth of conformal electrodes has been proposed [2]. Coolers utilizing vacuum nanogap were studied in a number of earlier works [3][4][5][6][7]. It has been shown that MVM junction cooling power is of the order of 100 W/cm 2 [3,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a conformal electrode method based on the electroplating of a top electrode has been proposed [2]. Coolers utilizing vacuum nanogaps have been studied in a number of earlier publications [3][4][5][6][7]. It has been shown that the cooling power of MVM junctions is high, on the order of 100 W/cm 2 [3,5].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, micro-coolers and energy converters based on electron tunneling have been investigated [1][2][3][4][5][6]. The earlier study of cooling by electron tunneling was conducted to prevent overheating in single-electron transistors [1].…”
Section: Introductionmentioning
confidence: 99%